Adaptation, Feasibility, and Acceptability of a Health Insurance Literacy Intervention for Caregivers of Pediatric Cancer Patients (CHAT-C) - Amy Chevrier; Perla L. Vaca Lopez; Katie Rogers; Monique Stefanou; Karely M. van Thiel Berghuijs; Douglas Fair; Elyse R. Park; Anne C. Kirchhoff; Echo L. Warner (Current Oncology)
We adapted CHAT, a four-session virtual program to help individuals affected by cancer manage insurance and medical costs for caregivers of pediatric cancer patients (called CHAT-C); we then pilot-tested CHAT-C. Eligible caregivers were ages 18+ and the primary caregiver to a pediatric cancer patient (≤25 years old) diagnosed in the past five years and treated at Primary Children’s Hospital. We conducted engagement studios to adapt the program. Feedback was evaluated using a rapid qualitative analysis framework and included content preferences, navigator preferences, logistics/structure, timing of delivery, and feasibility/acceptability. A small pilot test of CHAT-C was conducted; feasibility, acceptability, and preliminary efficacy were evaluated based on enrollment rates, qualitative feedback, and baseline/follow-up surveys. Participants in the pilot (n = 14) were primarily white (93%), married (93%), female (86%), ages 40–49 (50%), and college-educated (57%). Most participants (64%) completed all four sessions of CHAT-C. Those who did not complete the sessions cited a lack of time, a child’s disease progression, and a perceived lack of benefit. Health insurance literacy (measured by nine items) improved by 10.8 points on average (SD = 6.0, range: 9–36) after CHAT-C. Caregivers of childhood cancer patients are willing to participate in a health insurance program, but some caregivers need less time-intensive options.